PERBEDAAN JENIS UMPAN DAN WAKTU PENANGKAPAN KEPITING BAKAU (Scylla serrata) DENGAN BUBU LIPAT SKALA LABORATORIUM - Adi Susanto; Ririn Irnawati; Devi Yuliyanti (Jurnal Perikanan dan Kelautan, 2014)
Mud crabs fishing by using collapsible trap could be carried on day and night with different bait. Fishing time and bait affectivity have not been considered by fisherman. The objective to determine more effective fishing time and bait in laboratoty scale. The research was conducted in laboratory with Priacanthus tayenus, Upeneus sulphurus and cowhide as bait. Fishing time was divided into three parts, in the morning, afternoon and evening. Data was analyzed by Kruskal-Wallis. The result showed that the different bait and fishing time has significantly effect on the frequency and weight of mud crab that caught. Upeneus sulphurus is preferably bait than other bait and morning fishing time is the most effective than other time.Keyword: bait, capture time, collapsible trap, mud crab (Scylla serrata)